Enhanced moisture adsorption of activated carbon through surface modification - Haleema Mohamed Chulliyil; Iqra Reyaz Hamdani; Adeel Ahmad; Ahmed Al Shoaibi; Srinivasakannan Chandrasekar (Results in Surfaces and Interfaces, 2024)
Activated carbons are widely used as adsorbents in industries for various applications. The mechanism of moisture interaction with the industrial adsorbents is complex and yet to be clearly elucidated. The adsorption mechanism heavily depends on several parameters that include the pore size and distribution, surface chemistry, and treatment conditions. Various surface functional groups on the carbonaceous materials play a significant role in water adsorption, mainly the oxygen-containing functional groups (OFGs). A commercial mesoporous steam-activated carbon was subjected to surface modification on treatment with strong oxidizing agents and subjected to the adsorption of moisture. The isotherms were generated covering a temperature range of 30–50 °C. The adsorption capacity was observed to significantly improve post-treatment with oxidizing agents, while the effect was observed to be profound at lower partial pressures. A sharp increase in the moisture uptake indicates that the oxidized carbons have a higher affinity to moisture even at low concentrations and this could have a significant influence on the targeted molecules, since the moisture as a contaminant is expected to be present at low partial pressures. On the other hand, such a trend is highly favorable if carbon is to serve as a sorbent for the removal of moisture, as several-fold improvements in adsorption capacity were noticed as compared to virgin AC. Additionally, the adsorption capacity was also found to be significantly higher as compared to popular moisture adsorbents, such as silica gel and zeolites, especially at low partial pressures.